2018
DOI: 10.5018/economics-ejournal.ja.2018-64
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing for inventories with reference price effects

Abstract: This article presents a dynamic pricing model of a retailer selling an inventory, accounting for consumer behavior. The authors propose an optimal control model, maximizing the intertemporal profit with consumers sensitive to the selling price and to a reference price. The optimal dynamic pricing policy is solved with Pontryagin's maximum principle with a structural (general) demand function. The authors obtain an original pricing rule, which explicitly accounts for the impact of price and inventory on future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Hence, the general necessity and suitability based on a company's realistic market circumstances in any industry have not been researched yet, and a model was missing for business practitioners. This is consistent with Chenavez & Paraschiv's (2018) findings of the lack of a dynamic pricing model. However, while this research study has identified the overarching significance of the two factors brand advantage and delivered product benefits, Halttunen (2016) has rather discussed newly emerging factors like ease of use, access to the service, consumer's technological skills and others that may be added to the factors price and variety of choices.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, the general necessity and suitability based on a company's realistic market circumstances in any industry have not been researched yet, and a model was missing for business practitioners. This is consistent with Chenavez & Paraschiv's (2018) findings of the lack of a dynamic pricing model. However, while this research study has identified the overarching significance of the two factors brand advantage and delivered product benefits, Halttunen (2016) has rather discussed newly emerging factors like ease of use, access to the service, consumer's technological skills and others that may be added to the factors price and variety of choices.…”
Section: Discussionsupporting
confidence: 92%
“…Interested customers that visit the market place over time also observe the current market situation for a product and compare the offers of different sellers. The consumers' purchase decisions are typically based on their individual willingness-to-pay as well as on common reference prices, see, e.g., Popescu and Wu (2007) and Chenavaz and Paraschiv (2018). Reference prices can be based on prices of similar products or, in particular, on prices that have been observed in the past (cf.…”
Section: Dynamic Pricing Competition On Online Marketplacesmentioning
confidence: 99%
“…Dynamic pricing models that include reference price effects are studied by, e.g., Wu and Wu (2015), Popescu and Wu (2007), and Chenavaz and Paraschiv (2018). Dynamic pricing models in the presence of strategic customer behavior are analyzed by Levin et al (2009), Liu andZhang (2013), andSchlosser (2019).…”
Section: Related Workmentioning
confidence: 99%
“…The term -dynamic pricing‖ refers to a pricing model that entails altering the price of goods or services based on supply and demand or the characteristics of the customer (Wang, Tang, Zhang, Sun & Ziong, 2020). This model is growing in popularity within a wide variety of different industries due to its expected impact on revenues and corporate valuations (Brent & Gross, 2017;Chenavaz & Paraschiv, 2018;Cohen & Neubert, 2019;Drea & Narlik, 2016;Halkias, Neubert, Thurman, Adendorff & Abadir, 2020;Neubert, 2017;Wahyuda & Santosa, 2015;Xiong, Niyato, Wang, Han & Zhang, 2019). Throughout the course of the present paper, a systematic literature review relating to this form of pricing will be carried out.…”
Section: Introductionmentioning
confidence: 99%